Исследование ансамблей составных псевдослучайных последовательностей на базе функций Уолша и Голда - Попрыгин, А. А. (ХНУРЕ, 2019)
Orthogonal and correlation properties of the complex binary sequences that are based on Gould and M-sequences, providing large ensembles and acceptable correlation properties, and Walsh sequences that provide orthogonal properties were analyzed.